2020
DOI: 10.3847/1538-4357/ab7f2c
|View full text |Cite|
|
Sign up to set email alerts
|

On Stellar Evolution in a Neutrino Hertzsprung–Russell Diagram

Abstract: We explore the evolution of a select grid of solar metallicity stellar models from their pre-main sequence phase to near their final fates in a neutrino Hertzsprung-Russell diagram, where the neutrino luminosity replaces the traditional photon luminosity. Using a calibrated MESA solar model for the solar neutrino luminosity (L ν, = 0.02398 · L γ, = 9.1795 × 10 31 erg s −1 ) as a normalization, we identify 0.3 MeV electron neutrino emission from helium burning during the helium flash (peak L ν /L ν, 10 4 , flux… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 137 publications
4
20
0
Order By: Relevance
“…Farag et al (2020, see their Tables 1 and 2) showed that, if the above three input and target quantities are used, then the optimized solutions using the MESA code are similar to those in Vinyoles et al (2017). We confirmed that, using these three target quantities, we could reproduce exactly the results of Farag et al (2020). However, we found that in some cases this can result in values of Y surf outside the range of observed values (see, e.g., Table 4 of Vinyoles et al 2017).…”
Section: Chi-squared Testssupporting
confidence: 72%
See 1 more Smart Citation
“…Farag et al (2020, see their Tables 1 and 2) showed that, if the above three input and target quantities are used, then the optimized solutions using the MESA code are similar to those in Vinyoles et al (2017). We confirmed that, using these three target quantities, we could reproduce exactly the results of Farag et al (2020). However, we found that in some cases this can result in values of Y surf outside the range of observed values (see, e.g., Table 4 of Vinyoles et al 2017).…”
Section: Chi-squared Testssupporting
confidence: 72%
“…In the csv file, we list the values of M XY,lost [M ], assuming M Z,planet = 150 M ⊕ , and M Z,planet [M ⊕ ], assuming M XY,lost = 0, for the models with planet formation. Neutrino fluxes, calculated using the subroutine provided in Farag et al (2020), are also included in the csv file.…”
Section: Appendix A: Details Of Simulation Resultsmentioning
confidence: 99%
“…We take the NFW profile. ii ) The ν flux varies with the type and age of stars [27]. iii ) The star distribution in the Milky Way.…”
Section: < L a T E X I T S H A 1 _ B A S E 6 4 = " N P / R V H H E J ...mentioning
confidence: 99%
“…The abundance of 22 Ne when He-burning is completed is thus proportional to the initial CNO abundance of the progenitor main-sequence star. The weak reaction in this sequence powers the neutrino luminosity during He-burning (e.g., Serenelli & Fukugita 2005;Farag et al 2020) and marks the first time in a star's life that the core becomes neutron rich. For zero-age main sequence (ZAMS) masses between ;0.5 M e (Demarque & Mengel 1971;Prada Moroni & Straniero 2009;Gautschy 2012) and ;7 M e (Becker & Iben 1979, 1980García-Berro et al 1997), depending on the treatment of convective boundary mixing (Weidemann 2000;Denissenkov et al 2013;Jones et al 2013;Farmer et al 2015; Lecoanet et al 2016;Constantino et al 2015Constantino et al , 2016Constantino et al , 2017, the 14 N(α,γ) 18 F(,e + ν e ) 18 O(α,γ) 22 Ne reaction sequence determines the 22 Ne content of a resulting carbon-oxygen white dwarf (CO WD).…”
Section: Introductionmentioning
confidence: 99%